A history of Denmark from the Viking age to the 21st century - Hilson, Mary; Poulsen, Bjørn 1955-; Borring Olesen, Thorsten 1956- (Aarhus University Press, 2023)
"A history of Denmark depicts how Denmark, the Danish kingdom and the Danish state have developed and changed over more than a thousand years.In each of the book's nine chapters, researchers from Aarhus University focus on Denmark's political, cultural, social and international conditions. The authors describe the shift from the first joint Danish kings in the Viking Age and the medieval trinity of church, king and aristocracy over the arbitrariness of autocracy to today's democracy with a global outlook. They shed light on the ravages of plague epidemics, the social changes of the Reformation as well as the economic crisis in the interwar period, the accession to the EU and the increased military involvement in foreign conflict zones. It is a Danish story about the transformation from status and class society to welfare state, from peasant country to post-industrial society and from chroniclers to influencers. Based on the latest research, A Danish History provides a systematic presentation of Denmark's history."
Keywords: Geschichte 790-2022; Dänemark; Denmark / History; Denmark